2007
DOI: 10.1111/j.1440-1673.2006.01661.x
|View full text |Cite
|
Sign up to set email alerts
|

Acquired spontaneous intercostal abdominal hernia: Case report and a comprehensive review of the world literature

Abstract: Intercostal hernias develop most often as a result of a blunt or penetrating thoracoabdominal trauma. We know of no prior report of a spontaneously occuring intercostal hernia. This study presents a review of the published literature that deals with this uncommon phenomenon, along with a discussion of our patient's clinical presentation and imaging findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
45
0
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 21 publications
1
45
0
8
Order By: Relevance
“…4 However, there are several cases that have been described to be a consequence of a coughing-spell rib fracture, usu-ally in patients with other predisposing factors such as chronic obstructive pulmonary disease, asthma, advanced age, or osteoporosis. 1,3,4 The present report describes a case of a middleaged obese patient that developed a transdiaphragmatic intercostal hernia involving the liver and the ascending colon 6 months after a traumatic incident. The underlying mechanism, the anatomical and diagnostic considerations, as well as the treatment options are also discussed.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…4 However, there are several cases that have been described to be a consequence of a coughing-spell rib fracture, usu-ally in patients with other predisposing factors such as chronic obstructive pulmonary disease, asthma, advanced age, or osteoporosis. 1,3,4 The present report describes a case of a middleaged obese patient that developed a transdiaphragmatic intercostal hernia involving the liver and the ascending colon 6 months after a traumatic incident. The underlying mechanism, the anatomical and diagnostic considerations, as well as the treatment options are also discussed.…”
mentioning
confidence: 93%
“…[1][2][3] This condition is usually reported to occur following penetrating or blunt injuries of the thoracic wall. 4 However, there are several cases that have been described to be a consequence of a coughing-spell rib fracture, usu-ally in patients with other predisposing factors such as chronic obstructive pulmonary disease, asthma, advanced age, or osteoporosis.…”
mentioning
confidence: 99%
“…The inguinal, prepubic, and the paracostal areas present the largest incidence of abdominal hernias. Among the thoracic lesions, the diaphragm is the most affected, young male dogs being the most representative population (Moreno-Egea et al, 2007;Smeak, 2007;Unlu et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…In this case, laparoscopy allowed extensive observation of the abdomen and diaphragm, identification of the omentum as the only hernia content, and traction of this tissue. Unlu et al (2007), in a work conducted with human patients, found the omentum to be the main structure protruding into intercostal hernias, followed by the colon and small intestine.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation